Cultura nacional e cultura organizacional em hospitais: um estudo explorat??rio das subculturas dos hospitais no Brasil e nos EUA - Amaral, Augusto Carlos Patti do (2015)
The management of health care in general and hospitals in particular, is especially difficult in modern societies due to conflicts between conflicting values that resonate in these contexts (Goss, 1963; Stevenson, 2000). It is believed that these difficulties are expressed and resolved (if they are resolved in some way) in the culture or subculture of organizations that provide health care (Scott, Mannion, Davies & Marshall, 2003). Despite the intuitive relationship between national and organizational culture, empirical research linking the two phenomena are scarce. This paper compares the national and organizational cultures of Brazil and the United States and finds a significant, but complex. Clusters are found in the two countries that both replicate systematically reject as national values. In this paper uses an approach for the diagnosis of organizational culture in hospitals that explicitly deal with the conflicts between human relations, managerial effectiveness and technical capacity to learn as 9 hospitals - 4 in the US and 5 in Brazil - deal with the provision of health services. It appears that the verbal networks of such organizations form a center-periphery configuration instead of a hierarchical configuration. It is noted that there seems to be more variation in organizational cultures between hospitals within the studied than among countries own countries.